La réforme des institutions centrales. Quelques jalons - Beaudoin, Gérald-A. (Les Cahiers de droit, 1984)
« In this article the author envisages and studies the reform of the Senate, of the House of Commons and of the Supreme Court of Canada ; the function of the Governor General is also considered. A suggestion is made for introducing a system of mitigated proportional representation in the House of Commons, as proposed by the Pepin-Robarts report of January 1979. The authors analyses the advantages and disadvantages of an elected Senate, of a Senate whose members are appointed by the federal government or by the federal and provincial governments, of a second House which would constitute a House of the Provinces ; the author is aganist an equal representation of the provinces in the Senate. Professor Beaudoin favours a specialized constitutional Court of Canada, although he considers that such a reform is very unlikely to happen ; however, he adds that in any case, the Supreme Court is de facto a constitutional court to a certain extent. He recommends that the principle of dualism be more visible. Finally, the author describes how the function of Governor General has evolved since 1926, and outlines the role that the Governor General may play in normal and anormal times. »